2014
DOI: 10.4271/2014-01-1367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Transient Response and Turbocharger Coupling for High and Low Pressure EGR Systems

Abstract: The transient response of an engine with both High Pressure (HP) and Low Pressure (LP) EGR loops was compared by conducting step changes in EGR fraction at a constant engine speed and load. The HP EGR loop performance was shown to be closely linked to turbocharger performance, whereas the LP EGR loop was relatively independent of turbocharger performance and vice versa. The same experiment was repeated with the variable geometry turbine vanes completely open to reduce turbocharger action and achieve similar EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The tendency of the new homologation cycles, such as the Worldwide harmonized Light vehicles Test Cycles (WLTC) and Real Driving Emissions (RDE) cycles, will be more restrictive with transient operation which are more pollutant. For that reason, in parallel with the new homologation cycles, it is necessary to improve the control of emissions in transient operations [15]. Experimental and modeling tools were employed to fulfil this study.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of the new homologation cycles, such as the Worldwide harmonized Light vehicles Test Cycles (WLTC) and Real Driving Emissions (RDE) cycles, will be more restrictive with transient operation which are more pollutant. For that reason, in parallel with the new homologation cycles, it is necessary to improve the control of emissions in transient operations [15]. Experimental and modeling tools were employed to fulfil this study.…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, with the EGR valves open, any fluctuations in the VGT rack position would also lead to fluctuations in the EGR mass flow, which eventually degrade the emissions and driveability. 15 In recent years, model predictive control (MPC) has gained the attention of researchers because of its capability in dealing with coupled nonlinear systems. 16,17 It transforms the control problem into an optimization problem and provides precise control of the manipulated objects while complying with the constraints of the manipulated variables.…”
Section: Introductionmentioning
confidence: 99%
“…Heuwetter et al 16,17 combined LR and SR EGR systems on a General Motors Z19DTH 1.9l Euro 4 specification diesel engine equipped with a variable geometry turbine (VGT) to achieve low emissions and fuel consumption without sacrificing transient response capability due to the long EGR path. The authors concluded that hybrid EGR resulted in reductions in almost all recorded emissions for both steady state and transient operation.…”
Section: Introductionmentioning
confidence: 99%